Holistic and dynamic approach and methodology to establish and support multifunctional community seedbanks - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Over the years, Bioversity International has developed an holistic and dynamic approach and methodology to establish and support community seedbanks. This approach/methodology is now being taken up by others in countries around the world. In Africa, this is done by CCAFS and international/national partners, in Kenya, Uganda, South Africa, Zambia.